The 25th Annual General Meeting of Malaysian Economic Association - Ungku Abdul Hamid, Ungku Abdul Aziz (NIL, 1988)
Prof Diraja Ungku Aziz received the notice of the 25th Annual General Meeting of Malaysian Economic Association